Vedolizumab Safety During Pregnancy and Lactation in a Patient with Ulcerative Colitis: A Case Report - Pinto, Fernanda Patrícia Jeronymo [UNESP]; Dutra, Renata de Medeiros [UNESP]; Almeida, Livia Cafundo [UNESP]; Craveiro, Marcela Maria Silvino [UNESP]; Baima, Julio Pinheiro [UNESP]; Saad-Hossne, Rogerio [UNESP]; Sassaki, Ligia Yukie [UNESP] (Taylor & Francis, 2024)
Background: Inflammatory bowel disease (IBD) affects young adults of reproductive age, and questions related to pregnancy and breastfeeding are common in clinical practice. Most medications used to treat IBD are considered safe during pregnancy, except methotrexate and small molecules such as tofacitinib. Despite few studies regarding vedolizumab (VDZ) safety, it appears to be safe during pregnancy. Therefore, this study aimed to report the management of ulcerative colitis in pregnant patient refractory to anti-tumor necrosis factor (TNF) agents using VDZ. Case Report: A female, 38 years old, with ulcerative colitis was refractory to conventional treatment with mesalazine, sulfasalazine, and azathioprine. She was hospitalized at six weeks of gestation with severe acute colitis requiring the use of infliximab (IFX) to induce remission. She had a spontaneous abortion at nine weeks of gestation after the second dose of IFX. Since there was no endoscopic improvement after six months of IFX treatment, VDZ treatment was initiated. During the VDZ infusion period, the patient discovered that she was pregnant with twins, leading to the discussion of the risks and benefits of continuing the VDZ. The patient presented with disease clinical remission with the use of VDZ, and the babies were born at 34 weeks of gestation without complications. Breastfeeding was also performed without complications. Conclusion: Continued VDZ medication is safe during pregnancy and breastfeeding, with adverse events similar to anti-TNF therapy.
Keywords: biological therapy; gestation; inflammatory bowel disease; safety